Virtual Noise Based Detection in Cooperative Systems with Co-Channel Interference - Aslan, Hayri; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2016)
In this paper, we have investigated the effect of cochannel interference on Decode-and-forward based cooperative communication system by providing the analytical results and computer simulations over Rayleigh fading channels. Virtual noise technique is used with co-channel interference at relay and destination terminals. It can be clearly observed that virtual noise techniques provides full diversity gain for proposed system. The accuracy of the analytical results shown by computer simulations.
Keywords: Cooperative communication system; Virtual noise technique; Co-channel interference; Decode and forward; DIVERSITY; NETWORKS; Engineering